2016
DOI: 10.1002/fld.4218
|View full text |Cite
|
Sign up to set email alerts
|

A stabilized Nitsche‐type extended embedding mesh approach for 3D low‐ and high‐Reynolds‐number flows

Abstract: SUMMARYThis paper presents a stabilized extended finite element method (XFEM) based fluid formulation to embed arbitrary fluid patches into a fixed background fluid mesh. The new approach is highly beneficial when it comes to computational grid generation for complex domains, as it allows locally increased resolutions independent from size and structure of the background mesh. Motivating applications for such a domain decomposition technique are complex fluid-structure interaction problems, where an additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(63 citation statements)
references
References 50 publications
0
63
0
Order By: Relevance
“…A spatial semidiscrete cut finite element formulation of , which utilizes a stabilizing residual‐based variational multiscale (RBVM) concept in the interior of the domain, ie, SUPG/PSPG/LSIC terms (see, eg, the works of Gresho and Sani and Hughes et al) and ghost penalty (GP) terms in the boundary zone, is based on previous works and reads as follows.…”
Section: Finite Element Formulations—different Spatial Discretizationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A spatial semidiscrete cut finite element formulation of , which utilizes a stabilizing residual‐based variational multiscale (RBVM) concept in the interior of the domain, ie, SUPG/PSPG/LSIC terms (see, eg, the works of Gresho and Sani and Hughes et al) and ghost penalty (GP) terms in the boundary zone, is based on previous works and reads as follows.…”
Section: Finite Element Formulations—different Spatial Discretizationsmentioning
confidence: 99%
“…Studies on the proposed GP terms comprised in scriptGhGP can be found also in the cited works. Applications successfully utilizing this technique can be found, for example, in the works of Schott et al…”
Section: Finite Element Formulations—different Spatial Discretizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Definition For the weak coupling of the two subdomain approximations on scriptThnormalf1 and scriptThnormalf2, specified by the coupling constraints , the stabilized Nitsche‐type formulation from the work of Schott et al is applied, which is comprised in the following coupling operator: scriptChnormalf1normalf2()()Uh1,Uh2,()Vh1,Vh2=2pt⟨⟩2μnormalfbold-italicϵ()bold-italicuhnormalf2bold-italicnnormalf1normalf2,bold-italicvhnormalΓnormalf1normalf2+⟨⟩phnormalf2,bold-italicvh·bold-italicnnormalf1normalf2normalΓnormalf1normalf2 12em+2pt⟨⟩bold-italicuh,2μnormalfbold-italicϵ()bold-italicvhnormalf2bold-italicnnormalf1normalf…”
Section: A Cutfem‐based Hybrid Fsi Formulationmentioning
confidence: 99%
“…Concerning detailed accuracy, stability, and convergence results of the single key ingredients of this novel hybrid method, at this point, we would like to refer the interested reader to important and helpful preceding publications. The C ut FEM‐based fluid‐fluid coupling has been already investigated in the work of Schott et al in very detail. The latter includes numerical results for different Nitsche weighting and penalty variants, detailed convergence results in a large range of mesh sizes in two and three spatial dimensions.…”
Section: Numerical Examplesmentioning
confidence: 99%